A Bis-Glycosylamine Strategy for the Synthesis of Dimeric Iminosugars Based on a DAB-1 Scaffold - Kamilia Ould Lamara; Nathan Noël; Fabien Massicot; Jean-Luc Vasse; Stéphane P. Vincent; Jean-Bernard Behr (Molecules)
A straightforward synthetic route towards DAB-1 scaffolded dimeric iminosugars is described here, starting from readily available bis-glycosylamines. The method allows the integration of a variety of linkages (aryl, alkyl, polyethyleneglycol chains) between both iminosugars through the choice of the bis-amine used in the first step. Moreover, an additional substituent (allyl, ethynyl) may be inserted into the structure via nucleophilic addition of an organometallic reagent to the starting bis-glycosylamine. A symmetrical ethynyl-iminosugar proved susceptible to intramolecular Glaser coupling, affording the corresponding macrocyclic structure. Dimeric iminosugars were tested towards a series of commercial glycosidases to uncover potencies and selectivities when compared to DAB-1, their monomeric counterpart. Whereas a significant drop in inhibition potencies was observed towards glucosidases, some compounds displayed unexpected potent inhibition of β-galactosidase.